F(r)icções goesas : vários mundos numa só vida - Domingues, Evandro Luis Von Sydow (2008)
The present study analyses three literary works the short stories of Monção, by Vimala Devi, and the novels Um Estranho em Goa, by José Eduardo Agualusa, and O Último Olhar de Manú Miranda, by Orlando da Costa from the perspective of writing Goa, proposed by Ackbar Abbas (2002) in a study about Hong Kong, and here adapted to the context of the former Portuguese colony. Such a perspective, besides enlarging the concept of Goan or Indo-Portuguese literature, allowed Goa to be seen as a cultural space open to discussions and interpretations. Before the analysis of the fictional works itself, the existence of a literary system in Portuguese language in Goa was discussed, since 1510 when the region became a Portuguese colony until the present day. The analysis of Monção enabled the examination of a certai n ideological discourse often carried through the so-called colonial literature. The emphasis is on how the short stories obliterate colonial ideologies and discourses, which insisted / insist on the myths of cross-cultural encounters. With the analysis of the novels, the focus was on the moments of hybridizations, either in the content of the stories representations and configurations , or in their structures, since one can talk about the renewal of the novel as a genre, in Agualusa, and in a mix-bred Bildungsroman, in Orlando da Costa.